2021
DOI: 10.1002/vms3.496
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial pathogens identified from houseflies in different human and animal settings: A systematic review and meta‐analysis

Abstract: Housefly (Musca domestica) is an excellent candidate for the distribution of susceptible and resistant bacterial strains that potentially threaten public health. To date, there is a paucity of information on the global distribution of pathogenic bacteria of medical and veterinary importance from diverse environmental settings. Therefore, this study was undertaken to conduct a systemic review and meta-analysis to estimate occurrence of various bacterial species of medical and veterinary importance harboured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 85 publications
1
7
0
Order By: Relevance
“…In this study, 10 bacteria were isolated from the guts of housefly larvae, including Enterobacter , Providence , Pseudomonas , Lactococcus , Klebsiella , Bacillus and Acinetobacter . The composition of gut bacteria of the larvae was mostly consistent with the results reported in our previous research, and the differences may have been caused by the differences in feeding conditions and larval sources ( 21 ). Through the feeding experiment, it was found that the growth index of housefly larvae fed with Luria-Bertani liquid medium was significantly higher than that of flies fed with sterile water because the Luria-Bertani liquid medium contained artificially prepared nutrients for the growth of microorganisms, insects and animals, which had a beneficial impact on the development of housefly larvae, while sterile water was only used to maintain the lives of the larvae.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, 10 bacteria were isolated from the guts of housefly larvae, including Enterobacter , Providence , Pseudomonas , Lactococcus , Klebsiella , Bacillus and Acinetobacter . The composition of gut bacteria of the larvae was mostly consistent with the results reported in our previous research, and the differences may have been caused by the differences in feeding conditions and larval sources ( 21 ). Through the feeding experiment, it was found that the growth index of housefly larvae fed with Luria-Bertani liquid medium was significantly higher than that of flies fed with sterile water because the Luria-Bertani liquid medium contained artificially prepared nutrients for the growth of microorganisms, insects and animals, which had a beneficial impact on the development of housefly larvae, while sterile water was only used to maintain the lives of the larvae.…”
Section: Discussionsupporting
confidence: 89%
“…Traditional microbiological methods such as culture isolation using the spread plate technique are still considered the gold standard for diagnostic tests since they efficiently allow the identification of different bacterial species [ 56 ]. Generally, the International Organization for Standardization (ISO-6579, 2002) recommends classical microbiological culture isolation for the identification of Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of traditional culture isolation and molecular methods accurately identify bacterial pathogens [ 58 ]. Moreover, research has also shown that using molecular methods (PCR) reveals more identification of bacterial pathogens than traditional culture-based methods [ 56 , 58 ]. In this study, we observed that PCR appears to be the most utilized diagnostic method in the detection of Salmonella serovars/isolates with a prevalence of 72.1%, as employed in about 15 studies with over 4219 samples screened.…”
Section: Discussionmentioning
confidence: 99%
“…Diptera, speci cally ies, are considered signi cant environmental health pests due to their ability to transmit pathogens through primarily mechanical means, with some instances of biological transmission [1,2]. This insect group possesses abundant body and foot hairs that facilitate the transportation of various microorganisms, including bacteria such as Escherichia coli(E. coli), Staphylococcus aureus, Klebsiella spp, Bacillus spp, and Acinetobacter spp [3][4][5][6][7][8], as well as viruses like Adenoviruses and Rotaviruses [3,9], and a diverse array of parasites such as Cryptosporidium [9][10][11][12]. Within the subfamily Cyclostomatidae, several families hold signi cant importance in relation to human health, including Muscidae, Calliphoridae, Sarcophagidae, and Drosophilidae, totaling approximately 305 species [13].…”
Section: Introductionmentioning
confidence: 99%